DESAIN ANGGARAN PADA JENJANG PENDIDIKAN PRA SEKOLAH DI TK AISYIYAH BUSTANUL ATHFAL PURBAYAN KOTAGEDE - Nadilla Aleyda Maqhfira Agustin; Ainun Wafiq; Shaleh Shaleh (MPI STAI Sangatta Kutai Timur, 2025)
This research aims to understand the Traditional Budgeting System in preschool settings at TK ABA Purbayan Kotagede, Yogyakarta, to support the holistic Islamic Muhammadiyah program and address small-scale budgeting inefficiencies through operational aspects, revenue, and expenditure. The method employed in this study is a qualitative phenomenological approach focused on the school principal’s experiences, with data collected through observations, interviews, and documentation. Data analysis follows the Miles, Huberman, and Saldana model: condensation through data selection and simplification, presentation via thematic grouping, and triangulation for validity. The research findings indicate that the Traditional Budgeting System serves as a real-time fund allocation mechanism, with the principal’s role integrating EMASLIM as educator, manager, administrator, supervisor, leader, innovator, and motivator in the allocation process to support the amar ma’ruf nahi mungkar program, real-time oversight, and stakeholder participation, thereby enhancing accountability. However, its implications include rigidity in adapting to environmental dynamics, such as inflation or Merdeka Curriculum regulations, which may lead to long-term inefficiencies compared to alternative models like Zero-Based Budgeting (ZBB), Planning-Programming-Budgeting System (PPBS), and Performance-Based Budgeting, which are more flexible and results-oriented. Overall, this budgeting design enhances the preschool's operational sustainability.